Foundations of information and knowledge systems : 10th International Symposium, FoIKS 2018, Budapest, Hungary, May 14-18, 2018, Proceedings /: 10th International Symposium, FoIKS 2018, Budapest, Hungary, May 14-18, 2018, Proceedings. (2018) - Unknown
No abstract available